Molecular Pathways in Virus-Induced Cytokine Production - Mogensen, Trine H. (American Society for Microbiology, 2001)
Virus infections induce a proinflammatory response including expression of cytokines and chemokines. The subsequent leukocyte recruitment and antiviral effector functions contribute to the first line of defense against viruses. The molecular virus-cell interactions initiating these events have been studied intensively, and it appears that viral surface glycoproteins, double-stranded RNA, and intracellular viral proteins all have the capacity to activate signal transduction pathways leading to the expression of cytokines and chemokines. The signaling pathways activated by viral infections include the major proinflammatory pathways, with the transcription factor NF-κB having received special attention. These transcription factors in turn promote the expression of specific inducible host proteins and participate in the expression of some viral genes. Here we review the current knowledge of virus-induced signal transduction by seven human pathogenic viruses and the most widely used experimental models for viral infections. The molecular mechanisms of virus-induced expression of cytokines and chemokines is also analyzed.